Demographic modeling of optimal founder composition for white-rumped shama (Copsychus malabaricus) in captive breeding - YILDIRAY HAIDAR JABBAR; BURHANUDDIN MASY’UD; YANTO SANTOSA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Jabbar YH, Masy’ud B, Santosa Y. 2026. Demographic modeling of optimal founder composition for white-rumped shama (Copsychus malabaricus) in captive breeding. Biodiversitas 27 (6): d270625. https://doi.org/10.13057/biodiv/d270625. Birdkeeping is a popular cultural and economic activity in Indonesia, with the white-rumped shama among the most valuable species. However, the influence of founder composition on economic performance and conservation potential remains underexplored. This study aimed to evaluate the simulated optimal founder composition, estimate the resulting sustainable harvest and release outputs, and evaluate its financial feasibility. The study gathered data from four breeding facilities and one cricket farm in West Java and Aceh, Indonesia, and applied a deterministic age-structured Leslie matrix model to a 20-year projection, followed by a financial feasibility analysis under synthesized cost assumptions. Under the model assumptions, the simulation results show that for 10 monogamous breeding pairs, representing a medium-scale system, the scenario composed entirely of reproductive adults with a composition of 9 pairs in age class C (>2-3 years) and 1 pair in age class D (>3-4 years) produced the highest potential cumulative harvest, yielding 926 individuals over 20 years, including a potential release output of 41 individuals for potential reinforcement of wild populations. Financial analysis using a 6-12% discount rate showed that this scenario generated an NPV of IDR 116,135,510-292,329,127; a BCR of 1.21-1.40; an IRR of 20.00%; and a DPP of 6.00-7.48 years, indicating financial feasibility. These simulation-based findings demonstrate that optimizing founder composition can simultaneously enhance economic performance and captive population management for conservation, while the conservation benefits remain contingent on successful release and post-release evaluation.